Assignment of Canadian Defined Daily Doses and Canadian Defined Course Doses for Quantification of Antimicrobial Usage in Cattle - Lardé, Hélène; Dufour, Simon; Archambault, Marie; Léger, David; Loest, Daleen; Roy, Jean-Philippe; Francoz, David (Frontiers in Veterinary Science, 2020)
Standardized units are essential to allow quantification and comparison of antimicrobial usage (AMU) between species and regions. In Canada, defined daily and course doses have not yet been harmonized for cattle. Our objective was to assign defined daily and course doses (named DDDbovCA and DCDbovCA respectively) for cattle in Canada, by antimicrobial agent (AM) and by route of administration, based on the label of all products containing at least one AM, marketed and authorized in Canada for use in cattle. In April and December 2019, a systematic search was performed from the online Drug Product Database of Health Canada to identify veterinary products containing at least one AM, marketed in Canada for use in cattle. Products were divided by route of administration (intramammary, intrauterine, injectable, oral, and topical). The monograph was retrieved for each product from the Drug Product Database, or from the Canadian Edition of the Compendium of Veterinary Products, and read completely to extract recommended dosages in cattle. Standard weights were applied to compute doses if required. DDDbovCA and DCDbovCA were assigned by calculating an average of daily and course doses respectively, by AM and route of administration. Two products were excluded from calculations because of their claim as growth promotion or feed efficiency (no longer authorized in Canada for certain categories of AM). Overall, 39 injectable, 75 oral (including 23 medicated premixes), 8 intramammary (4 for lactating cows and 4 for dry cows), 5 intrauterine, and 4 topical products were used for calculations. DDDbovCA and DCDbovCA values were assigned successfully for each AM identified, by route of administration. These metrics will allow harmonized and transparent quantification of AMU in cattle in Canada.